Spaces for creativity and innovation within and across organizational boundaries - Oliver, Amalya L.; Sydow, Jörg; Cohendet, Patrick (Research in the sociology of organizations, 2025)
This volume contains an Open Access chapter. Delving into how the locus of creativity and innovation with new knowledge, products or processes takes place, while crossing organizational boundaries into what was termed "in-between spaces", the edited volume Spaces for Creativity and Innovation Within and Across Organizational Boundaries showcases the new organizational theoretical approaches and research questions that emerge from this focus on social interactions' spaces of different kind. Featuring multiple perspectives on this topic, the chapters focus on resources such as time and structure, and how they act as enabling as well as constraining factors in collaborative processes, the puzzling relevance of constraints in creative processes, and temporary or permanent experimental spaces. Additionally, analyzing the social networks that are formed in the creative and innovative space within or across organizational boundaries, the authors investigate how these networks can vary by structure and membership over time, or by the exchange processes they capture. Demonstrating that for the creative process to unfold and become institutionalized another level of interactions needs to be included, the volume shows how creative processes critically rely on the 'middleground', which consists of intermediary groups and communities that link the informal communities of the underground with formal organizations of the upperground. Tackling challenges that can enable and constrain creative and innovative processes in such in-between spaces such as issues of intellectual capital and trust and issues of competition and collaboration, this edited collection looks ahead to how we can create thriving spaces for creativity and innovation within and across organizations.